Android phones & tablets - Gookin, Dan (Hoboken, NJ John Wiley & Sons, Inc, 2018)
"Getting a smartphone or tablet is more enjoyable when you have an informative and entertaining guide to assist you! Whether you're upgrading from an older model or totally new to the complex world of Android devices, this book makes it easier than ever to get up and running with the latest and greatest technology. From setup and configuration to taking advantage of all those intricate bells and whistles, you'll want to keep this go-to reference close by every step of the way"--Publisher
Your own Android. An out-of-the-box experience ; The on-off chapter ; Android tour ; Type to type, text to edit -- Stay Connected. Telephone stuff ; Forward calls, missed calls, and voicemail ; The address book ; Text me ; You've got email ; Web browsing ; Digital social life -- Amazing Android Feats. There's a map for that ; Everyone say "cheese!" ; Your digital photo album ; Music, music, music ; Various and sundry apps ; Google play shopping -- Nuts and Bolts. It's a wireless life ; Connect, share, and store ; Apps and widgets ; Customize and configure ; Android security ; On the road again ; Maintenance, troubleshooting, and help -- The Part of Tens. Ten tips, tricks, and shortcuts ; Ten things to remember -- Index
Includes index
1
Keywords: Android (Electronic resource); Android (Electronic resource); Android (Electronic resource.); COMPUTERS -- Hardware -- Mobile Devices; Mobile apps -- Handbooks, manuals, etc; Mobile apps; Mobile computing -- Handbooks, manuals, etc; Mobile computing; Smartphones -- Handbooks, manuals, etc; Smartphones; Tablet computers -- Handbooks, manuals, etc; Tablet computers; Application software -- Development; Mobile computing; Handbooks and manuals; Handbooks and manuals